Chalcogen‐Bond Catalysis: Telluronium‐Catalyzed [4+2]‐Cyclocondensation of (in situ Generated) Aryl Imines with Alkenes. Issue 15 (7th February 2023) - Groslambert, Loic; Padilla‐Hernandez, Andres; Weiss, Robin; Pale, Patrick; Mamane, Victor
Abstract: In the chalcogen series, tellurium species exhibit the strongest chalcogen bonding (ChB) interaction with electron‐rich atom. This property explains the renewed interested toward tellurium‐based derivatives and their use in different applications, such as organocatalysis. In this context, the catalytic activity of telluronium salts in the Povarov reaction is presented herein. Different dienophiles, as well as imines of variable electronic nature, efficiently react in the presence of catalytic amount of either diarylmethyltelluronium or triaryltelluronium salts. Both catalysts could also readily perform the three‐component Povarov reaction starting from aldehyde, aniline and dihydrofuran. The reactivity of telluroniums towards imines and aldehydes was confirmed in the solid state by the ability of Te atom to interact through ChB with the oxygen carbonyl of acetone, and in solution with significant shift variations of the imine proton and of the tellurium atom in 1 H and 125 Te NMR spectroscopy. For the most active telluronium catalysts bearing CF3 groups, association constants ( K ) with N ‐phenyl phenylmethanimine in the range 22–38 M −1 were measured in dichloromethane. Abstract : Telluronium salts bearing electron‐withdrawing groups were prepared, and their ability to drive chalcogen bonds with ketones and imines was demonstrated in the solid state and in solution. These strong σ‐hole bond donors were able to efficiently catalyze the Povarov reaction through chalcogen bond activation of imines and subsequent reaction with alkenes. The title reaction was found to be as efficient with pre‐formed or in situ generated imines.